(untitled) (Global Journal of Human-Social Science, 2017)
This paper aims to show the closer link exists between the natural environment and economic development. It argues environment is a foundation for economic development. It is obvious that nature provides us with natural resources by which we humans can satisfy our desires. But, the problem is, humans go beyond a limit, and intervene in nature. The concentration of carbon dioxide has increased since the pre-industrial era primarily due to the combustion of fossil fuels and deforestation. Environmental degradation and environmental change have, therefore, threatened people’s health, physical security, material needs and social cohesion. Therefore, improper exploitation of natural resources and unlimited intervention in the natural environment jeopardizes the sustainability of any development.